2018
DOI: 10.1016/j.bbagen.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterisation of the Equilibrative Nucleoside Transporter family of Trypanosoma cruzi: ultra-high affinity and selectivity to survive in the intracellular niche

Abstract: This study reports the first cloning of T. cruzi purine and pyrimidine transporters, including the first gene encoding a pyrimidine-selective protozoan transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 74 publications
(6 reference statements)
3
41
1
1
Order By: Relevance
“…We have previously shown that it was possible to predict the substrate selectivity of Trypanosoma cruzi ENT transporters by analysing their phylogenetic alignment with ENTs from other kinetoplastids [ 32 ]. Figure 1 A shows a phylogenetic tree of nucleoside and nucleobase transporters from a number of different gene families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that it was possible to predict the substrate selectivity of Trypanosoma cruzi ENT transporters by analysing their phylogenetic alignment with ENTs from other kinetoplastids [ 32 ]. Figure 1 A shows a phylogenetic tree of nucleoside and nucleobase transporters from a number of different gene families.…”
Section: Resultsmentioning
confidence: 99%
“…To do so, we used a gain-of-function approach utilizing T. brucei as the expression system, as previously done by us for ENT family transporters of T. congolense , T. cruzi , Leishmania spp. and Trichomonas vaginalis [ 30 , 31 , 32 , 33 ]. We found Tg244440 to have high affinity for oxopurine nucleobases and nucleosides and only low affinity for aminopurines and pyrimidines.…”
Section: Introductionmentioning
confidence: 99%
“…To start assigning gene identities to the observed nucleoside and nucleobase transport activities of T. vaginalis trophozoites, each individual gene was to be expressed in a T. b. brucei strain, TbAT1‐KO, in which we had successfully characterized nucleoside transporters from several other protozoan species including Trypanosoma cruzi (Campagnaro, de Freitas Nascimento, et al., 2018), Trypanosoma congolense (Munday et al., 2013), Leishmania spp (Alzahrani et al., 2017), and Toxoplasma gondii (Campagnaro et al, manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…We find that the main transporters of T. vaginalis are able to take up purine nucleosides and pyrimidine nucleosides with similar affinity. In keeping with most protozoa no pyrimidine‐specific nucleoside transporters were identified (the sole documented exception is the T. cruzi NT2 transporter (Campagnaro, de Freitas Nascimento, et al., 2018)), although NT‐d did display higher affinity for uridine and thymidine than for adenosine and guanosine. Mixed purine‐pyrimidine nucleoside transporters have been described in Leishmania (Vasudevan et al., 1998) and Toxoplasma gondii (De Koning et al., 2003), whereas purine‐specific nucleoside transporters are the norm in T. brucei (De Koning & Jarvis, 1997, 1999) and Plasmodium falciparum (Quashie et al., 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Mammal cells use the de novo pathway to obtain purines (16) in their purinosomes (25). In contrast, fungi, bacteria (16), and parasitic protozoa like Plasmodium (26, 27), Entamoeba hystolytica (28, 29), Giardia lamblia (30), Toxoplasma gondii (31, 32), Trichomonas vaginalis (33), Trypanosoma cruzi (34), Trypanosoma brucei (3537), and Leishmania (38, 39), are purine auxotrophs, which lack the de novo metabolic route and obtain their purines and pyrimidines from imported DNA through salvage pathways.…”
Section: Nucleoside Hydrolases Are Key Enzymes For the Replication Ofmentioning
confidence: 99%